You are on page 1of 4

Basic Identities of Boolean Algebra

Boolean Algebra 1. X+0 = X 2. X.1 = X


3. X+1 = 1 4. X.0 = 0
5. X+X = X 6. X.X = X
Chapter 2-3 7. X+X’ = 1 8. X.X’ = 0
Z. Aliyazici 9. (X’)’=X
10. X+Y = Y+X
11. XY = YX (Commutative)
12. X+(Y+Z) = (X+Y)+Z (Associative)
13. X(YZ) = (XY)Z

Ex: Show that


a. (A+B)(A+CD) = A + BCD
14. X(Y+Z) = XY+XZ (Distributed) = A+ACD+BA+BCD
15. X+(YZ) = (X+Y)(X+Z) = A(1+CD+B)+BCD
= A1+BCD
16. (X+Y)’ = X’.Y’ (DeMorgan’s)
= A+BCD
17. (X.Y)’ = X’+Y’
b. (X+Y)(X+Z) = XX+XZ+XY+YZ
Ex: AB +C+1 = 1 = X+XZ+XY+YZ
X+(Y+Z) = (X+Y)+Z = X+Y+Z = X(1+Z+Y)+YZ
X(YZ) = (XY)Z = XYZ = X+YZ

Examples: Examples:
• XY+XY’=X(Y+Y’)=X Z=[A+B’C+D+EF][A+B’C+(D+EF)’]
• (X+Y)(X+Y’)=X+(YY’)=X Z=[ X + Y ][ X + Y’ ]
• X+XY’=X(1+Y’)=X Z=X=A+B’C
• X(X+Y)=X+XY=X(1+Y)=X
• (X+Y’)Y=XY+Y’Y=XY
• XY’+Y=(X+Y)(Y+Y’)=(X+Y)1=X+Y

• Z=A’BC+A’=A’(BC+1)=A’.1=A’

1
Standard Form Sum of product
• A Boolean function can be expressed in Sum of product form: all product are the
a different algebraic ways. product of single variables only
• The standard forms contain product Example:
terms and sum term
Example: F=XYZ is in product form use AND
AB’+CD’E+AC’E’ ABC’+DEFG+H
operations A

F=(X+Y)(X+Z)Z is in product form B

C
F=X+Y+Z is in logical sum form use OR D

gate E
A
F=XY+XZ+ZY is in sum form C
E

Product of Sums Example


• All sums are the sums of single variable (A+BC)(A+D+E) =A+AD+AE+ABC+BCD+BCE
=A(1+D+E+BC)+BCD+BCE
• Example: Product of sum
=A+BCD+BCE
• (A+B’)(C+D’+E)(A+C’+E’) Sum of product
• (A+B)(C+D+E)F Example:
AB’+C’D = (AB’+C’)(AB’+D)
• AB’C(D’+E) = (A+C’)(B’+C’)(A+D)(B’+D)
Sum of product
• Considered product of sums Product of sum

Algebraic Manipulation
F = X’YZ+X’YZ’+XZ X X’ X’YZ
= X’Y(Z+Z’) +XZ (by identity 14)
X’YZ’
= X’Y.1+XZ (by identity 7) Y F
= X’Y + XZ (by identity 2) Z Z’
XZ
X Y Z F F = X’YZ+X’YZ’+XZ
0 0 0 0
0 0 1 0 X X’ X’ Y
0 1 0 1 Y F=X’Y+XZ
0 1 1 1
1 0 0 0
1 0 1 1 Z XZ
1 1 0 0
1 1 1 1 F=X’Y + XZ

2
E.g., prove the theorem:

X • Y + X • Y' = X
• X(X+Y)=X+XY=X
X • Y + X •Y‘ = X • (Y + Y')
= X • (1)
=X • (X+Y)(X+Y’)=X+YY’+XY’+XY
=X+0+X(Y’+Y)=X+X(1)=X
E.g., prove the theorem:
X + X•Y = X?
• XY+X’Z+YZ=XY+X’Z ?
X + X•Y = X•1 + X•Y
= X • (1 + Y) XY+X’Z+YZ = XY+X’Z+YZ(X+X’)
= X • (1) = XY+X’Z+XYZ+X’YZ
= X
= XY+XYZ+X’Z+X’YZ
= XY(1+Z)+X’Z(1+Y)
= XY+X’Z

Inversion
• (A+B)(A’+C) = AA’+AC+BA’+BC Using DEMorgan’s Laws
= AC+A’B+BC (X+Y)’ = X’.Y’
= AC+A’B
X Y X+Y (X+Y)’ X Y X’ Y’ X’.Y’

0 0 0 1 0 0 1 1 1
0 1 1 0 0 1 1 0 0
1 0 1 0 1 0 0 1 0
1 1 1 0 1 1 0 0 0

Inversion
Using DEMorgan’s Laws • In general case, DeMorgen’s laws:
(XY)’ = X’+Y’ • (X1X2…XN )’=X1’+X2 ’+…+Xn’
• And
• (X1+X2+…+Xn )’=X1’X2’…Xn ’
X Y XY (XY)’ X Y X’ Y’ X’+Y’
Example:Find the inverse (complement) of
0 0 0 1 0 0 1 1 1 (A’+B)C’
0 1 0 1 0 1 1 0 1 [(A’+B)C’]’=(A’+B)’+(C’)’
1 0 0 1 1 0 0 1 1 =(A’)’(B’)+C
1 1 1 0 1 1 0 0 0
=AB’+C

3
Complement Function Duality
• Find the complement of the following function • Given a Boolean expression, replace
F1 = [X’YZ’+X’Y’Z]’ AND with OR, OR with AND, 0 with 1,
= (X’YZ’)’.(X’Y’Z)’ ad 1 with 0.
= (X+Y’+Z)(X+Y+Z’)
• Example:
– F=AB’+C+0D’(1+E)
F2 = [X(Y’Z’+YZ)]’
= X’+(Y’Z’+YZ)’ – FD=(A+B’)C(1+D’+0E)
=X’+(Y’Z’)’(YZ)’
= X’+(Y+Z)(Y’+Z’)
=X’+YY’+YZ’+Y’Z+ZZ’
=X’+YZ’+Y’Z

You might also like